2023
DOI: 10.1186/s12879-023-08435-1
|View full text |Cite
|
Sign up to set email alerts
|

The representative COVID-19 cohort Munich (KoCo19): from the beginning of the pandemic to the Delta virus variant

Abstract: Background Population-based serological studies allow to estimate prevalence of SARS-CoV-2 infections despite a substantial number of mild or asymptomatic disease courses. This became even more relevant for decision making after vaccination started. The KoCo19 cohort tracks the pandemic progress in the Munich general population for over two years, setting it apart in Europe. Methods Recruitment occurred during the initial pandemic wave, including 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…The risk factor analysis showed that HCWs had an increased risk of infection compared to the general population, which is interestingly consistent with previous research on the KoCo19 cohort and other studies that have identified HCWs as a vulnerable group for infection [ 30 , 44 , 54 ]. However, the use of PPE has been shown to reduce the risk of infection [ 44 ], possibly leading to a change in the risk of infection in HCWs over time.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The risk factor analysis showed that HCWs had an increased risk of infection compared to the general population, which is interestingly consistent with previous research on the KoCo19 cohort and other studies that have identified HCWs as a vulnerable group for infection [ 30 , 44 , 54 ]. However, the use of PPE has been shown to reduce the risk of infection [ 44 ], possibly leading to a change in the risk of infection in HCWs over time.…”
Section: Discussionsupporting
confidence: 89%
“…This discrepancy in sample size raises concerns about the comparability of the two groups, as the underrepresentation of current smokers may introduce bias to the results. However, the lower risk of infection among current smokers aligns with similar findings from the analysis of the KoCo19 cohort [ 30 ]. Additionally, a recent study by Günther et al (2022) supports these findings, as it demonstrated that current smokers were nearly half as likely to test positive for SARS-CoV-2 antibodies compared to non-smokers [ 54 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…SN1 ). Comparing the data in this study and with experience gathered in our population-based studies in Munich, Germany 11 , it can be appreciated that one exposure to SARS-CoV-2 with a natural infection generally induces Anti-S values below a cutoff value centered in the middle of the antibody level range (shifted log-scale) as indicated with the vertical dashed line in Fig. 1a and b .…”
Section: Resultssupporting
confidence: 64%